Opposing Roles of Wild-type and Mutant p53 in the Process of Epithelial to Mesenchymal Transition - Semenov, Oleg; Daks, Alexandra; Fedorova, Olga; Shuvalov, Oleg; Barlev, Nickolai A. (Frontiers in Molecular Biosciences, 2022)
The central role of an aberrantly activated EMT program in defining the critical features of aggressive carcinomas is well documented and includes cell plasticity, metastatic dissemination, drug resistance, and cancer stem cell-like phenotype. The p53 tumor suppressor is critical for leashing off all the features mentioned above. On the molecular level, suppression of these effects is exerted by p53 via regulation of its target genes, whose products are involved in cell cycle, apoptosis, autophagy, DNA repair, and interactions with immune cells. Importantly, a set of specific mutations in the TP53 gene (named Gain-of-Function mutations) converts this tumor suppressor into an oncogene. In this review, we attempted to contrast different regulatory roles of wild-type and mutant p53 in the multi-faceted process of EMT.